Chirality Amplified: Long, Discrete Helicene Nanoribbons - Xiao, Xiao; Pedersen, Stephan K.; Aranda, Daniel; Yang, Jingjing; Wiscons, Ren A.; Pittelkow, Michael; Steigerwald, Michael L.; Santoro, Fabrizio; Schuster, Nathaniel J.; Nuckolls, Colin (ACS Publications, 2020)
Here we report the synthesis of two polyhelicene frameworks consisting, from end-to-end, of 18 and 24 fused benzene rings. The latter exhibits the largest electronic circular dichroism in the visible spectrum of any molecule. These shape-persistent helical nanoribbons incorporate multiple helicenes, a class of contorted polycyclic aromatic molecules consisting of ortho-annulated rings. These conjugated, chiral molecules have interesting chemical, biological, and chiroptical properties; however, there are very few helicenes with extraordinary chiroptical response over a broad range of the visible spectrum—a key criterion for applications such as chiral optoelectronics. In this report, we show that coupling the polyhelicene framework with multiple perylene-diimide subunits elicits a significant chiroptic response. Notably, the molar circular dichroism increases faster than the absorptivity of these molecules as their helical axis lengthens. Computational analysis reveals that the greatly amplified circular dichroism arises from exciton-like interactions between the perylene-diimide and the helicene moieties. We predict that even greater chiroptic enhancement will result from further axial elongation of these nanoribbons, which can be readily enabled via the iterative synthetic method presented herein
Keywords: Quiralidad; Absorption; Chirality; Circular dichroism spectroscopy; Molecules; Optical properties